Optic nerve ultrasound in idiopathic intracranial hypertension - K.S. Iegorova; L.V. Zadoianyi; L.L. Marushchenko (Journal of Ophthalmology, 2016)
Backup: Vision loss associated with secondary optic atrophy is the major complication of idiopathic intracranial hypertension (IIH). A potential for the development of severe visual impairment necessitates regular monitoring and determines the importance of ophthalmological examination in patients with this condition. Optic nerve ultrasound (ONUS) enables identification of IIH and monitoring of raised intracranial pressure (ICP) in these patients.